Spatial distribution and seasonal variation of fish larvae in the upper 200 m of the Philippine Sea - Fang, Chen; Wang, Xiaogu; Sun, Dong; Zhai, Hongchang; Zhang, Dongsheng; Liao, Guanghong; Wang, Chunsheng (Frontiers in Marine Science, 2023)
The Philippine Sea, owing to its complicated circulation pattern and the presence of numerous seamounts, is considered to be a hotspot for biodiversity and an important fishing ground. However, to date, few studies on ichthyoplankton in the Philippine Sea have been conducted. During the summer, autumn, and winter of 2020–2021, a series of investigations were conducted to study the spatial and temporal structure of fish larvae in the Philippine Sea. A total of 65 samples were collected by vertical hauling from a depth of 200 m to the surface. A total of 882 fish larvae representing 81 distinct taxa, 49 genera, and 23 families were identified. A seasonal pattern was also observed based on the differences in abundance and dominant taxa. The abundance of fish larvae was 11.35 ± 12.46 ind./100 m3 (mean ± sd.) in summer, 5.83 ± 7.03 ind./100 m3 in autumn, and 2.57 ± 2.73 ind./100 m3 in winter. The dominant species were Vinciguerria nimbaria, Encrasicholina punctifer, and Cyclothone sp. in summer, V. nimbaria, and Ceratoscopelus warmingii in autumn, and Diaphus spp., D. garmani, and Sigmops sp. in winter. A significant latitudinal variation in fish larvae assemblages was found via cluster analysis, and two geographic groups were separated by the northern boundary of the North Equatorial Current. In addition, the fish larvae species diversity also showed a significant latitudinal gradient in autumn, which disappeared in summer. Canonical correspondence analysis indicated that the structure of fish larvae assemblages was affected by average temperature, salinity, and net primary productivity in the upper ocean and sea level anomaly. All dominant species were associated with specific niche environments. This study suggests that latitudinal zonation of fish larvae also occurs in the oligotrophic low latitude Pacific Ocean and is enhanced in autumn. These results provide multi-seasonal baseline data of fish larvae assemblage in the upper Philippine Sea, being an important reference for the planning of marine protected areas in the high seas.